2009
DOI: 10.1158/1535-7163.mct-08-0620
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase-specific virotherapy in an animal model of human head and neck cancer

Abstract: Telomerase-specific replication-competent adenovirus, Telomelysin (OBP-301), has a human telomerase reverse transcriptase promoter that regulates viral replication and efficiently kills human cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…injections of OBP-301 dramatically inhibited the growth of KCCT873 tumors in vivo (15). The present study adds to the antitumor profile of OBP-301 in SCCHN tumor-bearing mice, showing that OBP-301 has antitumor activity against large tumors.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…injections of OBP-301 dramatically inhibited the growth of KCCT873 tumors in vivo (15). The present study adds to the antitumor profile of OBP-301 in SCCHN tumor-bearing mice, showing that OBP-301 has antitumor activity against large tumors.…”
Section: Discussionsupporting
confidence: 54%
“…We have previously reported that a 5-day i.t. administration of OBP-301 to nude mice bearing subcutaneous KCCT873 human SCCHN xenografts had significant antitumor activity (15). In the present study, we extend this work by assessing the antitumor activity of OBP-301 in advanced SCCHN tumors.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…As E1A expression correlates directly with overall virus efficacy, the ability of the host cell to permit expression would profoundly influence all subsequent parts of the life cycle. However, previous studies found that E1A expression does not correspond with CAR and hTERT expression; hence, the levels of expression vary widely and do not correlate with OBP-301 sensitivity (12,27). Furthermore, a recent report showed that OBP-702, in which a human wild-type p53 gene expression cassette was inserted into the E3 region of OBP-301 suppressed the viability of cancer cells more efficiently than OBP-301, inducing dual apoptotic and autophagic cell death (28,29).…”
Section: Discussionmentioning
confidence: 99%
“… 73 OBP-301 induces tumor-selective oncolysis and antitumor effect in a telomerase-dependent manner in various cancer cells; eg, head and neck cancer, human bone and soft tissue sarcomas, and prostate cancer. 74 76 This vector injected into the primary tumor might be effective in purging micrometastasis from regional lymph nodes in an orthotopic colorectal cancer model. 77 OBP-301 enhances the sensitivity of various cancers to chemotherapy; eg, lung cancer, ovarian cancer.…”
Section: Therapeutic Potential and Clinical Utility Of The Replicatiomentioning
confidence: 99%